Comparison of meropenem with amikacin plus ceftazidime in the empirical treatment of febrile neutropenia: a prospective randomised multicentre trial in patients without previous prophylactic antibiotics - (:unkn) unknown (ELSEVIER, 1999)
Eighty three patients with neutropenia and cancer were randomised to receive either 1 g meropenem tds or amikacin 15 mg/kg single dose daily plus ceftazidime 2 g tds. No prophylactic antibiotics were allowed before entry to the trial. Seventy seven patients were available for analysis. Infection was microbiologically or clinically documented in 53 episodes (69%). The overall success rate without adjustment was 49% in monotherapy, 37.5% in the combination group. These rates were increased to 65% and 56%, respectively when secondary infection episodes requiring a different class of chemotherapy were taken into account. Median duration for defervescence was 3 days in successfully treated patients in both groups. Only minor reversible side effects were noted in both treatment arms. Meropenem monotherapy seemed as effective and safe as amikacin plus ceftazidime for the empirical treatment of neutropenic cancer patients with fever. (C) 1999 Published by Elsevier Science B.V. and International Society of Chemotherapy. All rights reserved.
Keywords: neutropenia; fever; cancer; meropenem; amikacin; ceftazidime; ESCHERICHIA-COLI BACTEREMIA; GRANULOCYTOPENIC PATIENTS; MONOTHERAPY; CANCER; FEVER; IMIPENEM; THERAPY